Managing childhood obesity, The Finnmark Activity School - Kokkvoll, Ane Sofie (UiT The Arctic University of Norway, 2014)
Paper number I of this thesis is not available in Munin: I: Ane Kokkvoll, Elisabeth Jeppesen, Petur B Juliusson, Trond Flægstad, Inger Njølstad, ‘High prevalence of overweight and obesity among 6-year-old children in Finnmark County, North Norway’, Acta Paediatrica, 2012, Volume 101, Issue 9, pp. 924–928. Available at http://dx.doi.org/10.1111/j.1651-2227.2012.02735.x Childhood obesity has reached epidemic proportions globally and represents a major threat to children’s health. Data on effectiveness of treatment programs for childhood obesity beyond one year is limited and there is little high-quality evidence to recommend one treatment over another. The objective of the clinical trial The Finnmark Activity School was to compare a new multidisciplinary approach comprising meeting with other families in groups and physical activity organised weekly (multiple family intervention, MUFI) with a more conventional single-family intervention (SIFI) with respect to primary outcome parameters (BMI kg/m2 and BMI SD score) and secondary outcome parameters (anthropometrical and psychological measures) up till two years of intervention ( Paper II and III). Both strategies were based on collaboration between specialised and primary health care. In order to enhance planning and recruitment process for an intervention study, we aimed at documenting the prevalence of childhood overweight and obesity within Finnmark county (Paper I).This thesis therefore comprises two studies; a cross sectional study of overweight and obesity prevalence and a clinical trial. A survey of 1774 children born during 1999 and 2000 collected from 18 child health care centres in Finnmark 2007, showed a prevalence of overweight (included obesity) of 16 % and 22 % among 6-year old boys and girls, respectively. The prevalence of overweight and obesity was high and justified preventive and treatment initiatives. Altogether 97 families were randomised in a parallel design, 91 delivered baseline data, height and weight data from 79 children were collected ...